The Effectiveness of the Tourism Master Plan (TMP 2013-2020) – Perceptions of Myanmar’s Tourism Stakeholder - John Ayoub (Centre For Tourism Planning and Development, 2020)
This paper is a work-in-progress that aims to assess the evaluation of the 2013-2020 Myanmar Hotel and Tourism Ministry (MHT) Tourism Master Plan (TMP 2013-2020) from the perceptions of the country's tourism stakeholders. The TMP aims to improve tourism outcomes through sustainable practices such as more practical education and training of industry staff as opposed to traditional rote learning methods which was a major concern discussed during the Australia-Myanmar Institute (AMI) conferences in Yangon and Mandalay in January 2020. Currently, much of Myanmar’s tourism infrastructure, namely accommodation, is limited to the Mandalay-Naypyidaw-Yangon corridor. A further challenge to the TMP will be the Covid-19 epidemic which has inhibited tourism activity. The research assessed the perceptions of Myanmar tourism stakeholders, including peripheral communities and international tour operators, using the extracted data to suggest calls-to-action in order to improve professional practice and lead to more sustainable tourism outcomes for Myanmar including its various remote and indigenous ethnicities.